Quality of life and psychological well‐being in obesity management: improving the odds of success by managing distress. Issue 3 (4th February 2016) - Vallis, M.
Summary: Background: Obesity is increasing in prevalence and placing an ever‐greater burden on individuals and healthcare resources alike. Obesity management is complex and, for many, elusive. Aims and methods: This paper reviews the major factors that influence psychological well‐being in individuals with obesity and describes the means by which their impact on distress and other aspects of quality of life (QoL) can be quantified. The goal is to enable healthcare providers to set reasonable, achievable, maintainable weight loss targets that will improve the psychological well‐being and QoL of individuals living with obesity. PubMed and Web of Science searches were conducted to identify literature that addresses the key question: How can distress over obesity be measured and taken into account when tailoring weight loss interventions for a particular patient? Discussion and conclusions: 'Distress over obesity' is a key parameter that illustrates the psychological consequences of excess weight. Healthcare providers can draw on a range of obesity‐specific and non‐specific assessment tools to quantify distress as well as the other contributions of obesity to QoL and mental/emotional health. When physicians consider the psychological/QoL aspects of obesity and how these change with successful weight loss, it becomes possible to set achievable, realistic weight loss goals and develop a manageable plan to achieve them. Any future developments that make it easier to achieve these goals should be made widely available to all patients in need, in order to help them turn a vicious cycle of failure into a virtuous cycle of success.